EURO-CORDEX: A Multi-Model Ensemble Fit for Assessing Future Hydrological Change? - Aitken, Gordon; Visser-Quinn, A.; Beevers, Lindsay (Frontiers in Water, 2022)
Human-induced changes in climatic behaviour and variations in future river flows has been at the fore-front of recent academic and political discourse. Future climate projections are a vital tool in tackling climate change and supporting future adaptation, however until recently models have been viewed individually with a lack of uncertainty quantification. A multi-model ensemble (MME) with a wide range of general circulation models, regional climate models and emissions scenarios, EURO-CORDEX provides climate projections as well as flow series projections across the European domain from 1950-2100. This paper explores the validity of the 68 chain MME flow projections by investigating its ability to match observed flow records in the UK over the period 1975-2004. The work explores magnitude through quantile matching and seasonality matching by time-series decomposition of trends. Two statistical tests (Mann-Whitney, and Mean Average Arctangent Percentage Error (MAAPE)) were used to compare EURO-CORDEX flow projections to observed river flows recorded by the National River Flow Archive (NRFA) across 1436 UK river catchments. Results indicate a high degree of similarity justifying the application of this dataset for assessing future hydrological changes across a regional scale. Discretising the flow projections into regional and hydrometric areas highlights the variability in performance between neighbouring domains and the strong influence local features may have on climate model performance. The validation of EURO-CORDEX flow projection data regionally enables a wide range of applications including the exploration of future changes in local and national river flows.